2020
DOI: 10.1183/16000617.0014-2020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of α1-antitrypsin PiZZ genotypes in patients with COPD in Europe: a systematic review

Abstract: The percentage of α1-antitrypsin protease inhibitor ZZ (PiZZ) genotypes in patients with COPD is controversial, with large differences among various studies. We aimed to estimate the prevalence of PiZZ in COPD patients from 20 European countries with available data, according to the number of PiZZ and COPD individuals in each country.A systematic review was conducted to select European countries with reliable data on the prevalence of PiZZ and COPD. We created a database with the following data: 1) total popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
(35 reference statements)
1
17
0
5
Order By: Relevance
“…We observed a large increase in AAT determinations during the study period with a total of 84 (2.4%) individuals being diagnosed with severe deficiency. Considering that the prevalence of severe AATD (specifically PI*ZZ) among the general population in Spain is only 0.03% 23 and among COPD patients in Europe it is 0.12%, 24 a detection rate of 2.4% for severe deficiency can be considered a good diagnostic yield. Moreover, more than half (57.6%) of the individuals tested carried an intermediate deficiency, which is highly relevant for the individual in order to prevent disease progression and to initiate family screening for early detection of affected relatives.…”
Section: Discussionmentioning
confidence: 99%
“…We observed a large increase in AAT determinations during the study period with a total of 84 (2.4%) individuals being diagnosed with severe deficiency. Considering that the prevalence of severe AATD (specifically PI*ZZ) among the general population in Spain is only 0.03% 23 and among COPD patients in Europe it is 0.12%, 24 a detection rate of 2.4% for severe deficiency can be considered a good diagnostic yield. Moreover, more than half (57.6%) of the individuals tested carried an intermediate deficiency, which is highly relevant for the individual in order to prevent disease progression and to initiate family screening for early detection of affected relatives.…”
Section: Discussionmentioning
confidence: 99%
“…A recent epidemiological study reported that the prevalence of Pi*ZZ/prevalence of COPD ratio in Europe was 0.12% (0.08-0.24%), differences being wide among the countries. 21 Numbers may be even higher in other countries; in Argentina, for example, the prevalence of AATD (Pi*ZZ or Pi*SZ) among COPD patients > 40 years of age was found to be 0.83%. 22 …”
Section: Epidemiologymentioning
confidence: 95%
“…Um estudo epidemiológico recente relatou que a relação prevalência de Pi*ZZ/prevalência de DPOC na Europa foi de 0,12% (0,08-0,24%), sendo as diferenças amplas entre os países. (21) Os números podem ser ainda maiores em outros países; na Argentina, por exemplo, constatou-se uma prevalência de DAAT (Pi*ZZ ou Pi*SZ) de 0,83% entre pacientes com DPOC e idade > 40 anos. (22) Em razão da ausência de estudos específicos, pouco se sabe sobre a epidemiologia dos alelos "raros" e "nulos" da DAAT, (7) que podem ser mais prevalentes do que se supunha anteriormente.…”
Section: Genéticaunclassified
See 1 more Smart Citation
“…An estimated 3.4 million people worldwide are affected; however, under diagnosis means many individuals remain undetected so this number is likely to be higher, highlighting the need for screening programmes in at risk individuals. 6,7 There are over 120 reported mutations in this gene, with the most common being the S and Z mutations, which affect 1.4 million and 250,000 people worldwide, respectively. 8 Both mutations result in misfolding of the protein, with the S variant resulting in a proportion of the AAT protein (~40%) being retained within hepatocytes, which reduces plasma levels but may not affect susceptibility to either liver or lung disease.…”
Section: Introductionmentioning
confidence: 99%